Reading acts theologically - Walton, Steve (Library of New Testament studies, 2022)
"Steve Walton collects several of his key essays into an expansive and coherent perspective, focusing on the theological perspective of Acts while considering the book's nature and focus, its portrait of the early Christian communities and their mission in the culturally varied first-century world, and its major theological themes"--